Factors Associated With Cases Of Dermatitis In Children (Aged 11-18 Years) In The Working Area Of The Semula Jadi Community Health Center In Tanjungbalai City - Lutfia Nurfadilah Manurung; Nofi Susanti (Universitas Muhammadiyah Palu, 2026)
One of the most common skin health problems is dermatitis. Dermatitis can affect people of all races and ages, but it tends to be more prevalent in children. According to data from the International League & Societies in 2022, there were 130 million cases of dermatitis in the world. This study aims to identify factors associated with the incidence of dermatitis in children in the working area of the Semula Jadi Community Health Center in Tanjungbalai City. The method used is an observational quantitative analytical study with a case-control design approach. Data analysis was performed using univariate and bivariate analysis with the chi-square test using SPSS software. The study population consisted of 75 cases of dermatitis in children, with a sample size of 72 respondents, consisting of 36 cases and 36 controls. The selection was made using a two-proportion formula and applying inclusion and exclusion criteria. The sampling technique was simple random sampling. Data collection was conducted through questionnaires and observation sheets. The results showed a significant relationship between a history of allergies and cases of dermatitis (p = 0.015 < 0.005) in children, a significant relationship between personal hygiene and cases of dermatitis in children (p = 0.002 < 0.005), a significant relationship between knowledge and cases of dermatitis in children (p = 0.004 < 0.005), and a significant relationship between environmental sanitation and cases of dermatitis in children (p = 0.002 < 0.005). This study concluded that the factors of allergy history, personal hygiene, knowledge